Restaurant Customer-Based Brand Equity Dimensions during COVID-19 - Lozano, Jaya Sierras; Ornopia, Jerome V; Montalbo, Kyle Calapre (Journal of Business on Hospitality and Tourism, 2022)
Academia continues to make significant efforts to comprehend the factors affecting the growth of a brand and its durability in times of pressure. In the restaurant industry, companies place a high priority on developing and maintaining brand equity for brands are one of their most important assets. In 2020, COVID-19 lockdowns and restrictions disrupted business norms across the globe, especially in the restaurant industry where the in-person dining experience plays a significant role in the overall business strategy. This research analyzed the four dimensions of customer-based brand equity (CBBE) of restaurants during the COVID-19 pandemic. Survey questionnaires were distributed to 219 dine-in customers of ten different restaurants when Cebu, Philippines, a known booming ground for homegrown brands, was under the Modified Enhanced Community Quarantine (MECQ) status. The study revealed that Brand Loyalty was the lowest among the four variables in all ten restaurants during the COVID-19 pandemic. No significant difference was noted among the four dimensions of all the restaurants included in this study.